Religious and confessional identification and faith in God among the citizens of Serbia - Blagojević Mirko (Filozofija i Društvo, 2012)
The author presents and analyses, in regard with the subject, the data from a systematic sociological research study of religiosity of the citizens of Serbia which is relevant for the Republic of Serbia without Kosovo and Metohija. The study named “Religiosity in Serbia and the EU integration process” was conducted twice, in 2010 and 2011, by the Christian Cultural Centre from Belgrade with the financial assistance of the Konrad Adenauer Foundation and the Center for European Studies from Brussels. Before analysing the data, the author briefly discusses the various dimensions of religiosity. [Projekat Ministarstva nauke Republike Srbije, br. 1790409: Politike društvenog pamćenja i nacionalnog identiteta - regionalni i evropski aspekt]